Mapping educational innovation and knowledge dissemination: a global bibliometric study - Zatrahadi, M. Fahli; Bah, Yahya Muhammed; Istiqomah, Istiqomah; Gassama, Saikou; Magistarina, Elrisfa; Aden, Edris bin; Juwara, Kemo; Emovwodo, Silas Oghenemaro; Badjie, Haruna (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
From 2023 to 2025, 1,034 publications were examined for academic knowledge diffusion and educational innovation. This bibliometric analysis uses VOSViewer for data recovery, pre-processing, network extraction, normalization, and visualization. Due to its importance in educational innovation, many research clusters focus on